Fabrication of Carbon Paste Electrode Modified with Nanobentonite and Nano TiO₂ for Tartrazine Analysis by Cyclic Voltammetry - Indah, Rahmalia; Setiarso, Pirim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Tartrazine is a synthetic dye widely used in food products, and its usage needs to be strictly controlled due to potential adverse health effects. One of the methods employed to analyze tartrazine levels is cyclic voltammetry. This study modified carbon paste electrodes by incorporating bentonite and titanium dioxide (TiO₂) nanoparticles to achieve a low detection limit. This research aimed to investigate the effect of the working electrode composition consisting of carbon, bentonite nanoparticles, TiO₂ nanoparticles, and paraffin on the peak current response in the analysis of tartrazine, as well as to determine optimal measurement conditions, namely composition and pH. Bentonite nanoparticles were synthesized using the sonochemical method, while TiO₂ nanoparticles in the anatase phase were obtained commercially. Material characterization was conducted using Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). The electrode was optimized with a composition ratio 3:4:1:2 (carbon:nanobentonite: nano TiO₂:paraffin), resulting in a cathodic peak current of -5,43 × 10⁻⁵ A. The optimal conditions for tartrazine detection were found to be at pH 7. This study demonstrates the potential of nanomaterial-modified carbon paste electrodes for developing low-cost, sensitive, and eco-friendly electrochemical sensors, which can be applied to monitor synthetic dyes in food safety control rapidly.